Examining the quality of work life: Empirical testing indicators in the public organisation - Mohammad Reza Zahedy; Seyyed Asghar Jafari; Majid Ramezan (Annals of Human Resource Management Research, 2021)
Purpose: This study aimed to identify employees’ quality of work life indicators in public organisations and provide necessary context to improve system accountability and employees’ needs in organisations. Research Methodology: To identify quality of work life indicators, the authors studied theoretical research basics entirely and, by considering elites’ ideas, identified main indicators using a descriptive survey technique. Results: Based on the research findings, 15 constituents were identified as work life quality indicators. The research results indicate undesired quality of work life among employees in public organisations. Of the identified constituents, safe and healthy working conditions and organisational conflict are the most important, while job satisfaction and pay/benefits are the least important factors. Conclusions: The study identifies fifteen indicators of Quality of Work Life (QWL) in public organisations and finds that overall QWL remains relatively low, highlighting the need for improvements to enhance employee well-being and organisational performance. Limitations: The results only extend the understanding of the role of quality of work life in organisational effectiveness and have implications for human resource managers that may not be applicable for other positions. Contributions: The study results help organisations identify the elements that affect the QWL and help them plan to increase organisational effectiveness by increasing employee satisfaction and motivation.